Handbook of Crystal Growth Bulk Crystal Growth : Basic Techniques Part A, Bulk Crystal Growth : Growth Mechanisms and Dynamics , Part B - Rudolph, Peter (San Diego : Elsevier Science & Technology Books, 2015)
Annotation Presenting basic growth technologies and modern crystal cutting methods, this volume examines in particular the methodical fundamentals and development of technology in the fields of bulk crystallization on both industrial and research scales.
Scholarly & Professional
Keywords: Crystal Growth; Crystal Mechanisms and Dynsmics; Chemistry